2008
DOI: 10.1111/j.1365-2567.2007.02800.x
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 2 and nucleotide‐binding oligomerization domain‐2 play divergent roles in the recognition of gut‐derived lactobacilli and bifidobacteria in dendritic cells

Abstract: Summary The gut microbiota is vital in the maintenance of homeostasis in the gut immune system. Its diversity and composition play major roles in relation to allergies and inflammatory bowel diseases, and administration of lactic acid bacteria (LAB), such as lactobacilli and bifidobacteria, has positive effects on these pathologies. However, the mechanisms behind the beneficial effects are largely unknown. Here we reveal divergent roles played by Toll‐like receptor‐2 (TLR2) and nucleotide‐binding oligomerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
165
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(179 citation statements)
references
References 49 publications
13
165
1
Order By: Relevance
“…The bacterial stimulation caused maturation and cytokine production of the DCs, regardless of the recombinant cell surface antigens. Previous studies showed that maturation and the cytokine responses of mouse or human DCs were induced by lactobacilli in a species/strain-dependent manner (7,9,30,42). This is apparently the result of variation of the MAMP composition and structure (13,24,33).…”
Section: Discussionmentioning
confidence: 98%
“…The bacterial stimulation caused maturation and cytokine production of the DCs, regardless of the recombinant cell surface antigens. Previous studies showed that maturation and the cytokine responses of mouse or human DCs were induced by lactobacilli in a species/strain-dependent manner (7,9,30,42). This is apparently the result of variation of the MAMP composition and structure (13,24,33).…”
Section: Discussionmentioning
confidence: 98%
“…1). It has been reported that the intact cell structure of LAB is an important element in its immunomodulatory activity and that the mature bacterial cells in the stationary phase induce more Th1-type cytokines than the immature cells in the logarithmic growth phase (Shida et al, 2006;Zeuthen et al, 2008;Sashihara et al, 2007). In our examination, there was no difference in Th1-type cytokine induction between MN45 cultured over a long period of time (35 days) and a short period of time (2 days).…”
Section: Discussionmentioning
confidence: 99%
“…As the LAB used for screening experiments were cultured for 7 days, the cultures contained not only live bacteria but also dead bacteria, and bacteriolysis was assumed to have occurred. It has been reported that the immunomodulatory activity of LAB contributes to the intact structure of the cell (Zeuthen et al, 2008). Therefore, the culture time may influence the cytokine-induction activity of MN45.…”
Section: Screening Of Lab Strains That Increased Il-12 and Ifn-γ Prodmentioning
confidence: 99%
“…However, TLR2 also seems to be involved in some anti-inflammatory effects of probiotics. Immunobiotics can inhibit IL-12 production by macrophages (33) and dendritic cells (47) by TLR2-mediated recognition of lipoproteins and insoluble cell walls. Moreover, TLR2 can induce tolerance of LPS that is referred to as heterotolerance or cross-tolerance (26).…”
Section: Discussionmentioning
confidence: 99%